Nonresponse Bias on Inpatient Rehabilitation Hospitals’ Experience of Care Quality Measure Scores - Allen Walter Heinemann, PhD; Anne Deutsch, RN, PhD, CRRN; Dave Brewington, PhD; Linda Foster, PT; Karon Frances Cook, PhD; Ana Miskovic, BA; David Cella, PhD (Archives of Rehabilitation Research and Clinical Translation)
Objective: To describe the magnitude of nonresponse bias on inpatient rehabilitation facility (IRF) experience of care survey data in patients with neurologic disorders. Design: Cohort study of patients at 2 IRFs. Patients reported experience of care via an IRF-administered survey as part of routine operations approximately 2 weeks after discharge. A partially overlapping sample of research participants completed a similar survey approximately 2 weeks and 30 days after discharge. Setting: Two inpatient rehabilitation facilities. Participants: Patients aged ≥18 years with neurologic disorders who were discharged from 2 IRFs. Interventions: None. Main Outcome Measures: Experience of care data collected via an IRF Survey (self-report or proxy responses) and a Research Survey (self-report only). Results: Of the 1055 patients admitted during the study period who met the age and diagnosis criteria, 490 (46.4%) completed one or both of the surveys. Of the 325 IRF Survey respondents, 202 were self-report, 99 were proxy respondents, and 24 were unknown respondents. Only patients completed the Research Survey (N=285). One hundred twenty patients completed both surveys, of which 7 were proxy IRF Survey respondents. IRF Survey respondents had higher cognitive function than nonrespondents; patients with spinal cord injuries were more likely to complete the IRF Survey than other patients. There were no differences in the proportions of patients answering favorably on the IRF Survey (all respondents) compared with the Research Survey, except for physician communication and discharge information. Mutual information analysis revealed agreement between the scores produced by the 2 data sources. Conclusions: There were subtle, potentially important differences in quality measure results across surveys, reflecting the extent to which patients are encouraged to complete experience of care surveys. There was higher agreement on questions about global hospital perceptions than specific aspects of patients’ experience.